Investigating Science Distance Learning Strategies in COVID-19 and their Impact on SOD students in American Curriculum Schools in the UAE - El-Gazzar, Heba (2021)
In modern days, the attention towards technology is massive. For so many years, it has been acknowledged as an important tool in the field of education but it was never a central objective until now. Recently, the need to use technology appears more due to the current global crisis of coronavirus pandemic as a significant educational tool. The main purpose of this study is to examine the effect of using distance learning in the science subject on SOD students’ outcomes from the teachers’, students’, and parents’ perceptions on different cases of SOD students in some American curriculum schools in the UAE. The conduction of this research study has a relevant motive behind it as it clarifies and creates realization regarding the importance of the use of various technical skills in the on-line teaching process in combination with the positive effect they imprint on the students’ learning and attainment. This study explores some different ways the students can gain knowledge from home and interpret the impact and the need for using the technology in this case of the distance learning process. This research study accommodated SOD students in the middle school level subject of science through questionnaires provided to 100 teachers, and interviews with students and parents who represent their children, aiming to accomplish the needed documents that will enhance the analysis of the research questions. The results showed that forty-eight percent of the teachers completely concurred that E-learning needs more mindfulness among parents and students so it can give more advantages to students, and about the same percentage agreed while the rest saw that it does not require any sort of mindfulness. On the other hand, the guardians accepted that distance learning is useful for their kids and it gives diverse learning experiences in contrast with the conventional educating techniques.